Detection and molecular characterization of Babesia sp. in wild boar (Sus scrofa) from western Japan - Morikawa, Momoko; Mitarai, Sumire; Kojima, Isshu; Okajima, Misuzu; Hatai, Hitoshi; Takano, Ai; Shimoda, Hiroshi; Maeda, Ken; Matsuu, Aya; Yoshida, Ayako; Hayashi, Kei; Ozawa, Makoto; et al. (Ticks and Tick-borne Diseases, 2021)
Wild animals often act as reservoirs of tick-borne Babesia and Theileria spp., which cause piroplasmosis. Therefore, epidemiological investigations about the distribution of these parasites in wild animals are important for evaluating the transmission risk to humans and livestock. In this study, we surveyed Babesia and Theileria spp. infecting wild boar (Sus scrofa) in Kagoshima and Yamaguchi prefectures and Tsushima island, which are all in western Japan, and performed molecular genetic analyses on the samples. DNA was extracted from either blood or liver samples of wild boar captured in Kagoshima prefecture in 2015, 2016, and 2018 and from blood samples from wild boar captured in Yamaguchi prefecture in 2013–2015 and Tsushima island in 2018. PCR screening for the partial 18S ribosomal RNA gene (18S rRNA) of both Babesia and Theileria spp. in wild boar revealed that 63.9 % (140 of 219 samples) were positive. Sequencing of all positive samples revealed that they were all the same Babesia species. Subsequent phylogenetic analyses showed that the parasite is closely related to Babesia sp. previously detected in the hard tick, Amblyomma testudinarium in Kagoshima, and further analyses suggested that this species is genetically related to Babesia gibsoni. On the other hand, no Theileria were detected in any of the samples. In summary, we observed a high prevalence of B. gibsoni–like Babesia sp. in wild boar in western regions of Japan. The host range, distribution, pathogenicity, and life cycle of this protozoan should be further evaluated.